Field architecture for traffic and mobility modelling in mobility management. (13th September 2012) - Sun, Jingbo; Si, Hongbo; Wang, Yue; Yuan, Jian; Shan, Xiuming; You, Ilsun
Aggregate mobility modelling, studying macroscopic rule of human movement, benefits the performance of mobility management. This paper is primarily focused on establishing an architecture based on field theory, using scalar and vector field to describe traffic and mobility, respectively. On the basis of their temporal–spatial evolution, we try to discover the relationship between traffic field and mobility field. This field architecture fits for mobility management in large temporal–spatial scale, since it not only benefits qualitative analysis of traffic and mobility in the perspective of field, but also provides a theoretical foundation and insight for issues in mobile communication.